(untitled) (HIMALAYA, 2020)
Among Buddhist religious specialists in Ladakh, there were until recently people called manepa, the Ladakhi pronunciation of the Tibetan word manipa, literally ‘the one [who recites] mani’. In the western Himalayas the repertoire of these non-monastic practitioners not only contains the famous mantra dedicated to the Great Compassion Bodhisattva Chenrezi (Skt. Avalokiteśvara), but also dozens of biographies which imply liberation in the Buddhist sense of the word and which praise the victory of Dharma over heretics. The Masters of the mani mantra are tantrists who regard the fourteenth-century Tibetan saint Thangtong Gyalpo as their founding preceptor. Among other skills, they perpetuate a fascinating ritual known as pho ba rdo gcog (or rdo gshag), ‘breaking a stone [placed] on the stomach’, which is believed to have been performed for the first time by this great yogi to ward off evil and to avert misfortune. Though the manepa tradition is still alive in the Pin valley in Spiti, where these religious specialists are called buchen (literally ‘great son’), it died out a few decades ago in Ladakh when the last representatives of the two existing manepa lineages passed away without an heir to carry on the family tradition. Recently, however, Tsewang Dorje, the grandson of one of them, decided to revive the tradition. In this article, I trace his life story and, more broadly, the barely known history of the manepa of Ladakh.